Morphology study of the proximal femur in Malay population - Baharuddin, Mohd Yusof; Abdul Kadir, Mohammed Rafiq; Zulkifly, Ahmad Hafiz; Saat , Azlin; Abdul Aziz , Azian; Lee, Muhammad Hisyam (Sociedad Chilena de Anatomía, 2011)
Clinical practice in our country showed a lack of suitable implants that perfectly match the anthropometry of the local population. However, there have been no reports or comprehensive studies conducted to substantiate this argument. We therefore prospectively studied 120 hips from sixty subjects with an average age of 25±5.18 years old. The average weight and height were 61.48±13.84 kg and 1.65±9.63 m respectively. The exclusion criteria were pregnant woman, those who had injury to the hip joint, and those with implant or prosthesis. Four parameters were measured the femoral head diameter (FHD), femoral neck length (FNL), femoral neck width (FNW) and collo-diaphyseal angle (CDA). Statistical analysis showed no significant differences between left and right femora but significant differences were found between male and female subjects. The results for the male and female femurs are as follows FHD: 43.6±3.1 mm and 38.9±2.2 mm; FNL: 91.1±5.7 mm and 81.8±4.3 mm; FNW: 28.9±3.4 mm and 26.0±4.3 mm; CDA: 132.3°±3.4° and 129.9°±4.0°. This data could be used as a guideline to design a more suitable implant for the Malay population which covers most of the South East Asian countries.